Pengujian Sistem Identitas Digital Siswa Berbasis Blockchain untuk Keamanan dan Transparansi Menggunakan Black-Box Testing - Slam, Berta Erwin; Irawan, Feri; Efranda, Nolan; Herikson , Rifaldi (Journal Software, Hardware and Information Technology, 2025)
This study proposes a blockchain-based student identity card system as a secure and transparent solution for managing digital identities at the senior high school level. The system is designed to address various issues found in conventional identification methods, such as data forgery, physical card damage, and limited verification capabilities. Developed using the Laravel framework and integrated with a private blockchain network, student identity data is hashed and stored permanently. The digital identity is represented as a QR code printed on the student ID card. Identity verification can be performed independently through a web-based application without relying on a central authority. System evaluation was conducted through functional testing using the black-box testing method, as well as user testing to assess reliability, efficiency, and usability. Test results showed that the system was able to verify identities with an average QR code response time of less than 3 seconds and a login success rate of 98%. Therefore, the integration of blockchain technology into the web platform proves to be an innovative and feasible approach to modernizing student identity management. This system contributes to strengthening the digital transformation of secondary education in a secure, efficient, and decentralized manner.